How we applied sports biomechanics to the preparations for the Olympic Games - Wang, Q. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
Sports biomechanics in China was started in 1959 when a textbook entitled "Sports Biomechanics" by Donskoi was introduced to China from the former Soviet Union during the first ever workshop of sports biomechanics. The first sports biomechanics research laboratory was established in China Institute of Sport Science. Since then, most of the institutes and departments of physical education in China have opened sports biomechanics courses while many provinces have established their own sports biomechanics laboratories. The Ministry of Education made sports biomechanics a required course for physical education majors in 1980, and officially published the required contents of sports biomechanics courses for physical education majors in 1985. The interests of major funding sources for research in China and the support of the Chinese government were mainly in applied research in the last two decades. Applied research has gained much more recognition than basic science research. Although the Chinese government has increased its investments to basic science research in the last several years, there is still a lot of work to do to fill up the gap in the level and quality of basic science research between China and other well developed countries in the world. Sports biomechanics in China as a scientific research area is in the same situation as other scientific research areas in China. Currently, basic science research in sports biomechanics in China is mainly focused on the following areas: - Anthropometry, represented by studies on measurements of the human body inertial parameters using CT techniques - Biomechanical modeling of human body motions, represented by studies on the characteristics of the flow field surrounding swimmers - Biomechanical properties of skeletal muscles, represented by studies on the constitutive equation of the skeletal muscle contraction - Biomechanics of sports injures and rehabilitation, represented by studies on the wrist injures of baseball throwers - Computer simulation of sports techniques, represented by studies on the somersault and twist techniques in diving - Neuro-network theories and methods for sports technique analysis - Kinematic, kinetic, and EMG data collection techniques for sports technique analysis. These basic science studies are only a small portion of the research in sports biomechanics in China. It is very difficult for biomechanists in these areas to have significant breakthroughs because of the limitations in scientific techniques. In contrast to the basic science research in sports biomechanics, applied research in sports biomechanics has been obtained broad recognition in China because of the need of this kind of research in competitive sports in China. Chinese athletes and coaches have found that they need biomechanists to support their training for the Olympic Games and other international competitions. Applied biomechanical research, focused on training, is commonly accepted by Chinese athletes and coaches in a variety of sports, and has obtained sufficient funding from a variety of funding agents. Currently, applied sports biomechanical research in China is mainly focused in the following areas: - Sports technique analysis (diagnosis, optimization, and simulation) - Dynamic measurements and analysis of sports techniques and muscle forces - Bioelectronic measurements and analysis of the neuromuscular system - Sports injuries. The research techniques used in this areas include - image analysis, force analysis, bioelectronic signal analysis, biomechanics theoretical analysis.